Depressive symptoms and employment status change in South Africa: A longitudinal study - M. Muchemwa; T. Sodi (Acta Psychologica)
Depression is a growing public health concern in South Africa, particularly as the nation faces high unemployment rates and fluctuations in the labour market. This study examines the association between changes in employment status and levels of depression in South Africa over time. Using longitudinal data from the National Income Dynamics Study (NIDS) Waves 1–5 (2008–2017), we assess how transitions in employment—such as moving from employment to unemployment, unemployment to employment, continuous unemployment affect individuals' mental health. Results indicate that individuals who transitioned from employment to unemployment were more likely to experience depressive symptoms compared to those who remained continuously employed (OR = 1.202). Those who were continuously unemployed had an increased likelihood of experiencing depressive symptoms compared to continuously employed individuals (OR = 1.172). Individuals who transitioned from being unemployed to employed had higher depressive symptoms compared to the continuously employed (OR = 1.097). These findings highlight the mental health risks associated with employment status change. Targeted mental health support, such as counselling and therapy, is needed for both long-term unemployed individuals and newly employed workers. This support can be delivered through community-based mental health programmes and the integration of mental health services within the workplace.